Structural and physicochemical properties of polar lipids from thermophilic archaea - Ulrih, Nataša Poklar; Gmajner, Dejan; Raspor, Peter (Applied microbiology and biotechnology, 2009)
The essential general features required for lipid membranes of extremophilic archaea to fulfill biological functions are that they are in the liquid crystalline phase and have extremely low permeability of solutes that is much less temperature sensitive due to a lack of lipid-phase transition and highly branched isoprenoid chains. Many accumulated data indicate that the organism’s response to extremely low pH is the opposite of that to high temperature. The high temperature adaptation does not require the tetraether lipids, while the adaptation of thermophiles to acidic environment requires the tetraether polar lipids. The presence of cyclopentane rings and the role of polar heads are not so straightforward regarding the correlations between fluidity and permeability of the lipid membrane. Due to the unique lipid structures and properties of archaeal lipids, they are a valuable resource in the development of novel biotechnological processes. This microreview focuses primarily on structural and physicochemical properties of polar lipids of (hyper)thermophilic archaea.